Correlation of serum magnesium levels with severity of liver disease in cirrhosis patients - Mogalapu, Sai Samhitha; Sivaprakasam, Venkatesan; Balasubramanian, Umadevi Thirukonda (International Journal of Research in Medical Sciences, 2025)
Background: Chronic liver disease (CLD) patients are prone to micronutrient disturbances particularly magnesium secondary to malnutrition and disturbed hepatic metabolism which may further exacerbate liver dysfunction. The child-turcotte-pugh (CTP) score and the model for end-stage liver disease (MELD) are established indices for cirrhosis prognostication. The ail of the study was to estimate serum magnesium levels in patients with chronic liver disease and to examine the correlation between serum magnesium levels and the severity of liver disease, as assessed by the MELD and child-pugh scores. Methods: This cross-sectional observational study recruited 121 participants meeting the inclusion criteria over a period of six months. Informed consent was obtained. Basic investigations were done, including complete blood count, renal and liver function tests, PT-INR, and serum magnesium levels. MELD and child-pugh scores were calculated, and data analysis was performed using SPSS software. Results: The median age of the participants was 45 years, with 85.12% being male and the predominant etiology being alcohol-related liver disease. The prevalence of Hypomagnesemia was 58.33%. A statistically significant correlation was observed between lower magnesium levels and higher child-pugh class, particularly in class C patients. There was a significant negative correlation between magnesium levels and MELD scores. Conclusions: The findings underscore the need for further randomised controlled trials to evaluate the efficacy of magnesium supplementation in slowing disease progression and preventing cirrhosis complications. This potential treatment could significantly reduce morbidity and mortality, offering a promising outlook for the future of cirrhosis management.